1998
DOI: 10.1159/000022424
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Post-Stroke Dementia

Abstract: Twenty to 25% of stroke patients are demented after stroke, which makes stroke an important risk factor for dementia. However, the diagnosis of dementia is difficult and depends heavily on methodology. In this review, we describe pitfalls of diagnosis, the prevalence and incidence of dementia after stroke based on data from prospectively studied stroke cohorts, and the risk factors for post-stroke dementia that emerged from these studies. Finally, the course and prognosis of post-stroke dementia are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 47 publications
0
13
0
5
Order By: Relevance
“…3 The short-term prevalence of poststroke dementia, including cognitive impairment, has been reported in many studies. [4][5][6][7] Most studies have used various standardized diagnostic measures, Diagnostic and Statistical Manuals of Mental Disorders IV, or a Mini-Mental State Examination (MMSE) score of <24 as an outcome. In a systematic review of 73 articles including 21 hospital-based and 8 population-based cohorts (7511 patients), 8 it was reported that the overall rates of dementia in the first year after first-ever stroke were highly heterogeneous.…”
mentioning
confidence: 99%
“…3 The short-term prevalence of poststroke dementia, including cognitive impairment, has been reported in many studies. [4][5][6][7] Most studies have used various standardized diagnostic measures, Diagnostic and Statistical Manuals of Mental Disorders IV, or a Mini-Mental State Examination (MMSE) score of <24 as an outcome. In a systematic review of 73 articles including 21 hospital-based and 8 population-based cohorts (7511 patients), 8 it was reported that the overall rates of dementia in the first year after first-ever stroke were highly heterogeneous.…”
mentioning
confidence: 99%
“…Olgularda lamotrijin, gabapentin ve levetirasetam inme sonrası nöbetlerde anlamı etkinlik ve yüksek tolerabilite göstermeleri sayesinde ilk basamak tedavide uygun seçeneklerdir. 23 [33][34][35][36][37][38][39][40] İnme sonrası demans tanısı hem demansın, hem de inmenin tanısını içerir. Demanslı hastalarda inmenin klinik bulgularının saptanması zor olabilir.…”
Section: Düşmelerunclassified
“…По разным данным, на которые влияют методология исследования и такие характеристики, как возраст, количе-ство инсультов в анамнезе, наличие КР до инсульта, сроки обследования после развития инсульта, КР той или иной степени тяжести отмечаются у 35-83% пациентов [2,[11][12][13][14][15], постинсультная деменция -у 6-40% [10,13,16].…”
Section: л е к ц и яunclassified